Characterization of Two Brassinosteroid C-6 Oxidase Genes in Pea - Jager, Corinne E; Symons, Gregory M; Nomura, Takahito; Yamada, Yumiko; Smith, Jennifer J; Yamaguchi, Shinjiro; Kamiya, Yuji; Weller, James L; Yokota, Takao; Reid, James B (Plant physiology (Bethesda), 2007)
C-6 oxidation genes play a key role in the regulation of biologically active brassinosteroid (BR) levels in the plant. They control BR activation, which involves the C-6 oxidation of 6-deoxocastasterone (6-DeoxoCS) to castasterone (CS) and in some cases the further conversion of CS to brassinolide (BL). C-6 oxidation is controlled by the CYP85A family of cytochrome P450s, and to date, two CYP85As have been isolated in tomato (Solanum lycopersicum), two in Arabidopsis (Arabidopsis thaliana), one in rice (Oryza sativa), and one in grape (Vitis vinifera). We have now isolated two CYP85As (CYP85A1 and CYP85A6) from pea (Pisum sativum). However, unlike Arabidopsis and tomato, which both contain one BR C-6 oxidase that converts 6-DeoxoCS to CS and one BR C-6 Baeyer-Villiger oxidase that converts 6-DeoxoCS right through to BL, the two BR C-6 oxidases in pea both act principally to convert 6-DeoxoCS to CS. The isolation of these two BR C-6 oxidation genes in pea highlights the species-specific differences associated with C-6 oxidation. In addition, we have isolated a novel BR-deficient mutant, lke, which blocks the function of one of these two BR C-6 oxidases (CYP85A6). The lke mutant exhibits a phenotype intermediate between wild-type plants and previously characterized pea BR mutants (lk, lka, and lkb) and contains reduced levels of CS and increased levels of 6-DeoxoCS. To date, lke is the only mutant identified in pea that blocks the latter steps of BR biosynthesis and it will therefore provide an excellent tool to further examine the regulation of BR biosynthesis and the relative biological activities of CS and BL in pea.